Experimental Study on The Characterization of Pyrolysis Products from Bagasse (Saccharum Officinarum L.): Bio-oil, Biochar, and Gas Products - Siti Jamilatun; Joko Pitoyo; Shinta Amelia; Alfian Ma’arif; Dhias Cahya Hakika; Ilham Mufandi (Universitas Pendidikan Indonesia, 2022)
Sugarcane bagasse is one of the most abundant biomasses. This study aims to examine the characteristics of bagasse using a pyrolysis system to produce liquid, solid (Biochar), and gaseous. A fixed bed reactor was installed in pyrolysis with temperature variations from 300 to 600°C. The ultimate and proximate analysis was applied to evaluate the characteristic of bagasse. The experimental result found that the maximum bio-oil was obtained at a temperature of 550°C. Several characterizations were done, including gas chromatography and surface area analysis. The Levoglucosan compound of 78% area. The temperature effect on pyrolysis influenced the O/C ratio, H/C ratio, HHV value, and surface area of biochar. The High Heating Value was obtained from 16.698 to 18.496 kJ/kg. Biochar results indicated that the surface area, average pore size, and total pore volume are 180.3-198.0 m2/g, 1.42-4.33 nm, and 0.11-0.12 nm, respectively. The study also analyzed its composition in biochar.